A co-simulation method as an enabler for joint analysis and design of MAS-based electrical power protection and communication. (July 2013) - Li, Weilin; Luo, Min; Zhu, Lin; Monti, Antonello; Ponci, Ferdinanda
Multi-agent system (MAS) protection is under investigation as a potential method for distributed control in modern electrical power systems. The coordination of the MAS is based on local measurements available to each agent's site as well as on the information exchanged between agents over the communication network. Hence, the communication network should be considered to be a main factor in determining overall system performance. Numerical simulation is a fundamental tool of the design process. Existing electric power simulation tools can satisfactorily model traditional power systems where power and communication are considered to be decoupled and MAS are not present. Similarly, the simulation tools for communication systems have been developed independently from the application, particularly power system scenarios, so they are decoupled from the actual use of the information. If the loop between communication and power is closed and the coupling is strong, as in MAS-controlled power systems, such a simulation environment may yield unrealistic results. Aiming at filling this gap, this paper proposes a co-simulation solution for power systems, communication networks, and MAS, based on the extended capability of the co-simulation platform called VPNET. VPNET consists of three parts: Virtual Test Bed for time domain simulation of power systems, OPNET for the simulation of communication networks, and the Co-simulation Coordinator for data exchange and time synchronization between the other two simulators. The Co-simulation Coordinator has been exploited for MAS integration, as the rules of each agent are defined in the modules provided by the Co-simulation Coordinator. The proposed extended co-simulation platform is tested in the analysis of the performance of the MAS-based protection schemes of a medium-voltage DC shipboard power system. Numerical simulations have been performed for communication testing and protection testing. In the communication test, the network parameters (bandwidth and transmission time) are analyzed to evaluate the performance of the communication network under various conditions; in particular, links failure. The MAS-based protection system was then tested under various operating conditions of the communication network (latency and links failure). From the simulation results it can be seen that the designed MAS protection can handle these conditions successfully. Particularly in the link failure conditions, this co-simulation platform could simulate the re-routing process of the communication network and lead to correct protection performance, which is impossible with individual simulators alone. These simulation results show the utility of VPNET in exploring the design trade-offs between protection strategies and communication in the design phase.